Integrating Landscape Connectivity and Natural-Anthropogenic Interaction to Understand Karst Vegetation Restoration: A Case Study of Guizhou Province, China - Huang, Kexin; Peng, Li; Wang, Xiaohui; Chen, Tiantian (Frontiers in Ecology and Evolution, 2022)
Because of implementation of ecological projects, the restoration of vegetation not only changes the typological composition and spatial structure of the landscape, but also improves the regional ecosystem function. The present study considered the effects of natural-anthropogenic factors and landscape connectivity on vegetation restoration. It also explored the impact and underlying mechanisms by which structural changes in landscape connectivity affect vegetation coverage in the karst region of Guizhou Province and provided a novel perspective for the maintenance of regional ecological security. We used morphological spatial pattern analysis (MSPA) and integrated valuation of ecosystem services and tradeoffs (InVEST) and circuit theory to identify ecological networks and explore the changes in landscape structure. We performed a Theil-Sen Median trend analysis and a Mann-Kendall (MK) trend test to determine spatiotemporal variations in vegetation coverage. We conducted a coupling analysis to discover correlations between the average cumulative current density (CCD) and the normalized difference vegetation index (NDVI) in various karst landform counties. We also implemented a geographical detector to detect the factors affecting the NDVI trend and disclose interactions among factors. The results showed that (1) Though the total area of forests and core areas was reduced, the ecological networks and landscape connectivity steadily improved. (2) Areas with improved vegetation coverage accounted for 77.77% of the total. By contrast, the degraded areas covered 14.28% while the remaining 7.95% was stable. (3) The relationships between the average CCD and the NDVI were inconsistent among various geomorphological counties. The counties with the highest proportions of karst landforms presented with negative correlations between the average CCD and the NDVI in 2005 and positive correlations between these parameters in 2018. (4) The NDVI trend was influenced by several factors. Of these, anthropogenic activity played a dominant role. Nevertheless, changes in landscape connectivity was also implicated. Attention should be paid to the impact of landscape connectivity on ecological restoration. The foregoing results indicated that the rocky desertification projects effectively improved landscape connectivity and vegetation coverage and provided a reference for developing policies establishing and maintaining ecological security of the karst ecosystem and coordinating sustainable development in this region.